URGENSI MANAJEMEN BERBASIS SEKOLAH UNTUK MENINGKATKAN KURIKULUM DAN PEMBELAJARAN DI SEKOLAH DASAR - Irnanda, Ela; Putri, Riska Nanda; Suhendra, Irwan; Nurhizrah, Gustituati; Hadiyanto, Hadiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the urgency of implementing school-based management (SBM) as a strategy to improve curriculum and learning in primary schools through a literature review methodology. SBM is an approach that gives schools greater autonomy in decision-making, aiming to improve the quality of education through the active participation of principals, teachers, students and communities. The literature analyzed in this research includes various empirical and theoretical studies that examine the implementation of SBM and its impact on improving the quality of curriculum and learning. The results show that SBM contributes significantly to tailoring the curriculum to local needs, improving learning effectiveness, and creating a more responsive and innovative learning environment. The study also found that the success of SBM relies heavily on policy support, adequate training for educators and commitment from all stakeholders. Based on these findings, the study recommends increased support and resources for the implementation of SBM to achieve optimal results in basic education.